Penerapan Film Tipis Ba0.25Sr0.75TiO3 (BST) Yang Didadah Ferium Oksida Sebagai Sensor Suhu Berbantukan Mikrokontroler - Ardian, A.; Nady, L.; Erviansyah, R.; Syafutra, H.; Irzaman, Irzaman; Siswadi, Siswadi (BERKALA FISIKA, 2010)
Ferroelectric material originating from Barium Strontium Titanate (BST), is expected to have high energy because it has a dielectric constant and high charge storage capacity [6]. Materials produced by the process of ferium dopan, it is hoped will be a temperature sensor. If, materials BST and BFST (Barium Ferium Strontium Titanate) subjected to the temperature (material change that temperature), and the resulting voltage, then this material can be applied as a temperature sensor using a microcontroller. Microcontroller that used is ATMega 8535 with internal ADC. Voltage was generated, will be reinforced with a voltage amplifier (OpAmp) and will be processed into digital data at the ATMega8535 internal ADC (Analog Digital Converter).Incoming digital data will be processed and displayed in the view Microcontroller-based desktop applications Delphi 7. The material to be tested is material BST, BFST 5%, and BFST 15%. Keyword: BST, Temperature sensor, ATMEGA 8535, ADC, Delphi 7